2007
DOI: 10.1590/s1807-59322007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Time-Compressed Speech Test in Brazilian Portuguese

Abstract: Rabelo CM, Schochat E. Time-compressed speech test in brazilian portuguese. Clinics. 2007;62(3):261-72. INTRODUCTION:The time-compressed speech test has existed since the 1970s. It is sensitive for evaluating auditory closure. However, it is not used in Brazil because until recently, it had not been developed in Portuguese. PURPOSE: To develop a compressed speech test in Portuguese, to apply it to normal-hearing adults, and to verify which of the compressed lists (50%, 60%, or 70%) is the most appropriate to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 14 publications
5
32
2
6
Order By: Relevance
“…The average found in the time-compressed speech test (73.81% to the right ear and 72.36% to the left ear) for the elderly in the present study was below the standardization for Brazilian adults (90% of correct answers regardless of the ear) (12) .…”
Section: Resultscontrasting
confidence: 88%
See 4 more Smart Citations
“…The average found in the time-compressed speech test (73.81% to the right ear and 72.36% to the left ear) for the elderly in the present study was below the standardization for Brazilian adults (90% of correct answers regardless of the ear) (12) .…”
Section: Resultscontrasting
confidence: 88%
“…In this study, the authors found, for the same speech material and the same compression rate used in the present study, scores of 92.4% for the right ear and 91.8% for the left ear (12) .…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations